P20 The relationship between a trusted adult and adolescent health and education outcomes: A systematic review. (18th November 2019) - Whitehead, R; Pringle, J; Milne, D; Scott, E; McAteer, J
Abstract : Aims: The presence of social networks is recognised to be a protective factor for adolescents' health and wellbeing, with the role of 'trusted adults' recently coming into sharper focus. There is, however, little review-level evidence concerning such relationships. Aims: 1) Identify what constitutes a trusted adult. 2) Evaluate the association between trusted adults and adolescent health/education outcomes. 3) Identify how to establish/maintain trusted adult relationships. Methods: Search terms (e.g., 'trusted adult', 'natural mentor', 'supportive adult') were used to query 13 bibliographic databases.Inclusion criteria: adolescents aged 10-19 years; role of trusted adult, defined as 'someone who children and young people may turn to for help, and will take them seriously'; reports health/educational outcomes; published between 01/01/07 and 31/12/17; English language. Exclusion criteria: parenting programmes; focus on populations with specific pre-existing health/learning conditions. Results: Of 2, 908 retrieved articles, 192 met inclusion criteria. Most described primary quantitative studies (136 articles, including 14 randomised controlled trials) with 25 qualitative and 18 mixed-methods studies. Four meta-analyses, six systematic reviews, and three narrative reviews were also included. Whilst there exists no universal definition of the trusted adult role, commonly observed qualities include assistance with personal emotional problems, a close emotional bond and someone that 'makes an important positive difference'. Existing quantitative evidence provides an unclear picture of the association between trusted adult presence and adolescent outcomes, with reviews predominantly finding no overall effect or small effect sizes. A number of methodological issues were identified which may, in part, explain these modest and inconclusive findings. Chiefly, quantitative studies tend to use vague definitions of the trusted adult role. Qualitative studies are less ambiguous in this respect and tend to more frequently indicate a beneficial impact of the role. Barriers and facilitators to establishing a trusted adult relationship were identified. These suggest the youth work sector is particularly well placed as a setting to establish trusted adult relationships. Conclusion: Methodological limitations in existing literature mean it is difficult to make firm conclusions on the impact of the trusted adult role on adolescent outcomes. Recommendations are proposed for future research including the use of mixed-methods approaches.